Representações do corpo feminino em contos de O leopardo é um animal delicado, de Marina Colasanti - Pacheco, Victória Lopes (2021)
This dissertation has as its object of study the book of short stories O leopardo é um animal delicado (1998), by Marina Colasanti. Out of the twenty-five texts, eight were selected to compose this work: “É alma, não é?”, “Menina de vermelho a caminho da lua”, “Porque a pena”, “Um dia, afinal”, “Maria, Maria”, “O leopardo é um animal delicado”, “Na funda escuridão” e “Amor e morte na página dezessete”. We prioritized these narratives mainly because they are all centered on female characters, enabling the development of the discussion around them. Our objective, in the course of reading each of the chosen texts and analyzing the central characters, is to reflect on how these female characters are fictionally represented, based on the idea of corporeality proposed by Elizabeth Grosz ( 2000) and the body categories presented by Elódia Xavier in Que corpo é esse? (2007) – especially, eroticized body and immobilized body –, in addition to two other categories proposed in this dissertation – maternal body and sick body –, allowing an association with Declínio do patriarcado (1998), which will help us in our deliberations about family relationships. Throughout our investigations, we sought to establish a productive dialogue with some critical reception of Marina Colasanti's production and also with some theoretical-critical discussions arising from gender studies.